Penjatuhan Sanksi Bagi Anak Didik Pemasyarakatan Pasca Melarikan Diri (Studi pada Lembaga Pembinaan Khusus Anak Kelas II Ambon) - Deotrich Sammuel Sahetapy; Sherly Adam; Hadibah Zachra Wadjo (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: The imposition of sanctions for correctional protégés who escape from the Ambon Class II Special Guidance Institute for Children when the child is serving his criminal period.Purposes of the Research: The purpose of this article is to analyze and discuss the sanctions imposed on correctional students after escaping from the Special Development Institute of Children Class II Ambon.Methods of the Research: The research method used in this research is empirical juridical/sociological juridical, which is a type of research that aims to describe a statement that is in the field based on legal principles, legal rules or legislation that applies and has something to do with the problems that occur.Results of the Research: The results showed that the imposition of sanctions on correctional students after escaping from the Ambon Class II Children's Special Guidance Institute based on the classification of violations of the seriousness level including serious disciplinary violations and if adjusted to the type of disciplinary sanctions the actions of the correctional students were classified as severe disciplinary sanctions, so that the sanctions imposed were severe. imposed or given by the Ambon Class II Children's Special Guidance Institute to correctional students, namely the sanction of cleaning the bathroom.